(untitled) (Italian Journal of Public Health, 2012)
Background: according to ISTAT (National Institute of Statistics-Italy), in 2011 20.7% of the foreign population in Italy is composed by children, either coming along with their families or alone, like in international adoptions. Immigrant children have some peculiarities related to their previous living conditions, although there are no significant differences between immigrant and native children’ diseases. Methods: in 3.5 years we evaluated every adoptee that reached our university centre, by using GLNBI (Gruppo di Lavoro Nazionale del Bambino Immigrato) diagnostic – aiding protocol, in order to assess infectious diseases, nutritional deficiencies, immunization status, intestinal parasitosis or other pathologies; this protocol is actually applied only in research centres. Results: we evaluated 358 international adoptees from 4 different Zones of the world; average age at first visit was approximately 5 years. Health certifications concerning vaccination history records were considered “valid” in 59.2% (212/358), 49.5% (105/212) of which had a complete panel of immunization. QuantiFERON®_TB Gold In-Tube (QTF) test resulted negative in 94.0% cases (313/333) and positive in 6.0% (20/333). HIV, HCV and Syphilis tests resulted in 0.3% positive test for each serology (1/358). Cysticercosis’ serology was positive in 8.9% (32/358) using immunoenzymatic assay (not confirmed by immunoblotting) and Toxocariasis in 13.1% (47/358). Parasitological investigation of faeces were found positive on 42.7% (153/358) children, throat swabs in 11.5% (41/358) children. There were 82.4% (295/358) abnormal blood count, 41.9% (150/358) low ferritin, 89.9% (322/358) endocrine abnormalities and 20.4% (73/358) various pathologies evaluated by specialists. Conclusions: pathologies affecting our study group are the same affecting other categories of immigrant children, because they often share similar living conditions as orphanage or crowded residencies, low and poor intake of appropriate nutrients for growing ages, leading to malnutrition, vitamin D deficiency, iron deficiency anaemia and intestinal parasitosis. Vaccination records are often not available or reliable. A similar protocol could therefore be helpfully used as an initial management of children coming from a different setting.